Disassembly of Tau fibrils by the human Hsp70 disaggregation machinery generates small seeding-competent species - Nachman, Eliana; Wentink, Anne; Madiona, Karine; Bousset, Luc; Katsinelos, Taxiarchis; Allinson, Kieren; Kampinga, Harm; McEwan, William A.; Jahn, Thomas R.; Melki, Ronald; Mogk, Axel; Bukau, Bernd; et al. (JBC papers in press, 2020)
The accumulation of amyloid Tau aggregates is implicated in Alzheimer's disease (AD) and other tauopathies. Molecular chaperones are known to maintain protein homeostasis. Here, we show that an ATP-dependent human chaperone system disassembles Tau fibrils in vitro. We found that this function is mediated by the core chaperone HSC70, assisted by specific cochaperones, in particular class B J-domain proteins and a heat shock protein 110 (Hsp110)-type nucleotide exchange factor (NEF). The Hsp70 disaggregation machinery processed recombinant fibrils assembled from all six Tau isoforms as well as Sarkosyl-resistant Tau aggregates extracted from cell cultures and human AD brain tissues, demonstrating the ability of the Hsp70 machinery to recognize a broad range of Tau aggregates. However, the chaperone activity released monomeric and small oligomeric Tau species, which induced the aggregation of self-propagating Tau conformers in a Tau cell culture model. We conclude that the activity of the Hsp70 disaggregation machinery is a double-edged sword, as it eliminates Tau amyloids at the cost of generating new seeds.